New Physics from the Sky - AAVV, AAVV (Il Colle di Galileo, 2023)
The LHC and direct detection experiments have had the most interesting possible outcome: the observation of a Higgs boson in isolation. This has left a void in theoretical particle physics, making the traditional questions on the origin of the weak scale and on the nature of dark matter deeper and more confusing than ever. The field has responded by producing a number of ideas that trace the answer to these questions to the early history of the Universe. At the same time, a number of new probes of the evolution of the Universe are planned or are already recording data. This calls for a meeting place where particle physicists, astrophysicists and cosmologists can join forces to refine theoretical ideas, find new experimental targets and benefit from the expertise needed to answer the most pressing questions in fundamental physics. This workshop offered the particle physics community access to a wealth of present and future cosmological data. It also gave, to the astrophysics and cosmology communities, an overview of the latest ideas that connect their disciplines to the fundamental laws of particle interactions.